THE ROLE OF DIGITAL INTERACTIVE ACTIVITIES IN ENHANCING ENGLISH LANGUAGE LEARNING - Aydogdyyeva Tavus Dovletovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
In recent years, the integration of digital interactive activities into English Language Learning (ELL) has transformed traditional pedagogical approaches. These technologies, including gamified platforms, mobile applications, virtual simulations, and interactive multimedia tools, have significantly improved learners’ engagement, motivation, and language acquisition outcomes. This article explores the role of digital interactive activities in enhancing English language learning, focusing on how interactivity fosters communicative competence, learner autonomy, and meaningful language practice. Drawing on recent literature, the study highlights the effectiveness of digital tools in creating learner-centered environments that support active participation and reduce anxiety in language learning. The article also discusses challenges such as digital inequality, teacher preparedness, and overreliance on technology. Overall, the findings suggest that digital interactive activities are a powerful supplement to traditional instruction when implemented strategically.